2020
DOI: 10.1002/ajim.23116
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Occupational Safety and Health Administration (OSHA) noise standard violations over 50 years: 1972 to 2019

Abstract: Introduction: Noise exposure has long been an occupational health concern and has been an important area of focus of the Occupational Safety and Health Administration (OSHA) since its founding. Nevertheless, it remains unclear what effects OSHA's noise standards have had on employer efforts to reduce risks. Consequently, a review of OSHA noise standard violations was performed to clarify the violation trends between 1972 and 2019. Methods: Using the OSHA Information System, researchers identified 119 305 viola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…Para evitar los incidentes en el campo laboral es necesario aplicar las normas de seguridad OSHA. Al seguirlas, los trabajadores reducen el número de accidentes ocurridos o, en su defecto, la gravedad de muchas lesiones que ocurren por algún incidente (53,54).…”
Section: Figura 2 Mapa Mental Del Sistema De Seguridad Y Salud En áRe...unclassified
“…Para evitar los incidentes en el campo laboral es necesario aplicar las normas de seguridad OSHA. Al seguirlas, los trabajadores reducen el número de accidentes ocurridos o, en su defecto, la gravedad de muchas lesiones que ocurren por algún incidente (53,54).…”
Section: Figura 2 Mapa Mental Del Sistema De Seguridad Y Salud En áRe...unclassified
“…About 50 years ago, OSHA promulgated four Occupational Noise Exposure Standards: (a) 29 CFR 1910.95, Occupational noise exposure; (b) 29 CFR 1926.52, Occupational noise exposure; (c) 29 CFR 1926.101, Hearing protection; and (d) 29 CFR 1904.10, Recording criteria for cases involving occupational hearing loss. OSHA has also employed various approaches to manage NIHL at the individual company level 5 . Strong evidence exists for the effectiveness of a number of occupational health and safety regulations with respect to reducing injuries and occupational health disparities as well as improving compliance with applicable laws 6,7 .…”
mentioning
confidence: 99%
“…Moreover, studies evaluating enforcement tools have been insufficient, and only two studies have proposed the need for OSHA noise-related enforcement actions 9,10 . In an extensive literature review, we identified only one study that investigated the extent of violations of the above four OSHA Noise Standards to reveal violation trends between 1972 and 2019 5 …”
mentioning
confidence: 99%
See 2 more Smart Citations